Oh what entangled web we weave. (Economist, 2017)
The article discusses the advents in the fields of quantum physics and how the quantum networks may soon underpin unhackable communications links. The usage of quantum-encrypted transactions has been put to scrutiny as hackers have developed many new ways and have demonstrated that such transactions are vulnerable to attacks. The two cases of usage of quantum technology have also been presented, which include 2004's Bank of Austria's bank transfer and 2007's Swiss Federal Elections.